Manual of museum exhibitions - Piacente, Maria (A Lord Cultural Resources Book, 2022)
Drawing on years of experience, Maria Piacente details the exhibition process in a straightforward way that can be easily adapted by institutions of any size. She and her contributing authors explore the exhibition development process in greater detail, providing the technical and practical methodologies museum professionals need today.